Oxidative potential of gas phase combustion emissions - An underestimated and potentially harmful component of air pollution from combustion processes. (June 2017) - Stevanovic, S.; Vaughan, A.; Hedayat, F.; Salimi, F.; Rahman, M.M.; Zare, A.; Brown, R.A.; Brown, R.J.; Wang, H.; Zhang, Z.; Wang, X.; Bottle, S.E.; et al.
Abstract: The oxidative potential (OP) of the gas phase is an important and neglected aspect of environmental toxicity. Whilst prolonged exposure to particulate matter (PM) associated reactive oxygen species (ROS) have been shown to lead to negative health effects, the potential for compounds in gas phase to cause similar effects is yet to be understood. In this study we describe: the significance of the gas phase OP generated through vehicle emissions; discuss the origin and evolution of species contributing to measured OP; and report on the impact of gas phase OP on human lung cells. The model aerosol for this study was exhaust emitted from a Euro III Common-rail diesel engine fuelled with different blends of diesel and biodiesel. The gas phase of these emissions was found to be potentially as hazardous as the particle phase. Fuel oxygen content was found to negatively correlate with the gas phase OP, and positively correlate with particle phase OP. This signifies a complex interaction between reactive species present in gas and particle phase. Furthermore, this interaction has an overarching effect on the OP of both particle and gas phase, and therefore the toxicity of combustion emissions. Highlights: Gas phase emissions can be potentially as hazardous as the particle phase ones. Gas phase diesel exhaust has a stronger inflammation effect on human lung cells. Fuel oxygen content is negatively correlated to the gas phase OP. Total VOC content is not correlated to the gas phase OP. Idling produces emissions with the highest OP in the gas phase.